First record of genus Nabicerus Kwon (Hemiptera: Cicadellidae: Idiocerinae) from China, with descriptions of two new species - Xue, Qingquan; Zhang, Yalin (Zootaxa, 2014)
Nabicerus Kwon is reported from China for the first time based on two new species, N. dentimus and N. baculatus spp. nov., and a new Chinese record of N. fuscescens (Anufriev, 1971). Species of this genus are described and illustrated. A redescription of the genus is provided together with a checklist and key to species for the separation of males.